2011
DOI: 10.1016/j.talanta.2010.11.070
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of N-acetylcysteine in pharmaceuticals using cobalt phthalocyanine modified graphite electrodes

Abstract: Flow injection analysis (FIA) with amperometric detection was employed for the quantification of N-acetylcysteine (NAC) in pharmaceutical formulations, utilizing an ordinary pyrolytic graphite (OPG) electrode modified with cobalt phthalocyanine (CoPc). Cyclic voltammetry was used in preliminary studies to establish the best conditions for NAC analysis. In FIA-amperometric experiments the OPG-CoPc electrode exhibited sharp and reproducible current peaks over a wide linear working range (5.0×10(-5)-1.0×10(-3) mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…The results obtained from bare SPE were also given in Figure 1 for comparison. In sulfur containing a NaOH solution, the cyclic voltammetric response of bare SPE was featureless (Figure 1a), while in the presence of a CoPc modified SPE, a reproducible and well defined faradic response to sulfur was obtained at E pa − 0.30 V and E pc − 0.27 V ( vs. Ag/AgCl) (Figure 1b) in the potential range of − 0.2 V to 0.6 V. During the transfer of Co I to Co II and Co II to Co I for the cathodic and anodic peak, similar electrochemcal behavior was reported [26]. This observation clearly demonstrates an electro-catalytic mediation of the CoPc towards the sulfur oxidation reaction.…”
Section: Resultssupporting
confidence: 76%
“…The results obtained from bare SPE were also given in Figure 1 for comparison. In sulfur containing a NaOH solution, the cyclic voltammetric response of bare SPE was featureless (Figure 1a), while in the presence of a CoPc modified SPE, a reproducible and well defined faradic response to sulfur was obtained at E pa − 0.30 V and E pc − 0.27 V ( vs. Ag/AgCl) (Figure 1b) in the potential range of − 0.2 V to 0.6 V. During the transfer of Co I to Co II and Co II to Co I for the cathodic and anodic peak, similar electrochemcal behavior was reported [26]. This observation clearly demonstrates an electro-catalytic mediation of the CoPc towards the sulfur oxidation reaction.…”
Section: Resultssupporting
confidence: 76%
“…Flow injection analysis (FIA) with amperometric detection was employed for the quantification of N-acetylcysteine (NAC) in pharmaceutical formulations, utilizing an ordinary pyrolytic graphite (OPG) electrode modified with cobalt phthalocyanine (CoPc) [121]. Cyclic voltammetry was used in preliminary studies to establish the best conditions for NAC analysis.…”
Section: Modified Graphite Electrodesmentioning
confidence: 99%
“…For the flow injection analysis experiments, a simple flow cell was built in house (Fig. 6A) [121] in such a way as to fit the same pyrolytic carbon electrode previously employed in the voltammetric experiments. A miniaturized Ag/AgCl/KCl sat electrode was constructed in the laboratory for use in the same flow cell [122].…”
Section: Modified Graphite Electrodesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have revealed that NAC inhibits muscle fatigue and can be used to enhance performance in exercise and endurance training. [1][2][3] Analytical techniques like colorimetry, 4,5 chemiluminiscence, 6,7 electrochemical detection, [8][9][10][11][12][13][14][15] flurimetry, 16,17 turbidimetry and nephlometry, 18 liquid chromatography tandem mass spectrometry, 19-21-44 gas chromatography mass spectrometry, 22,23 and capillary electrophoresis [24][25][26] have been employed in literature for the quantification of acetyl cysteine. Acetyl cysteine has also been simultaneously quantified along with other drugs like clomiphene citrate, 27 arginine, 28 and cefexime trihydrate.…”
Section: Introductionmentioning
confidence: 99%